PATHOMORPHOLOGY OF ZERO BIOPSIES OF DONOR KIDNEYS - M. L. Arefjev; M. G. Minina; N. P. Mogeiko; I. M. Iljinsky (Вестник трансплантологии и искусственных органов)
There is well known fact that kidney transplants from Extended Criteria Donors may increase risk of De- layed Graft Function and Primary Non-Function of transplants. We have collected and tested 65 «zero» kidney biopsies from cadaver donors aged from 19 to 71 years old. In the pool of elderly donors who died from cerebrovascular accident the frequency of nephrosclerosis presentation was higher than in donors of yonger age who died from craniocephalic trauma. Nevertheless in the general donor pool the number of sclerosed glomeruli was no more than 12%. We did not meet at all in the whole volume of material any bi- opsy with the severe degree of arteriosclerosis. The «zero» biopsies of cadaver kidneys is quite usable and unexpensive tool to measure the degree of nephrosclerosis in order to exclude kidneys which are not fitable for transplantation.